Hydrogen derived from algae and cyanobacteria as a decentralized fueling option for hydrogen powered cars: Size, space, and cost characteristics of potential bioreactors. Issue 5 (3rd May 2020) - Kolbe, Karin; Lechtenböhmer, Stefan; Fischedick, Manfred
Abstract: New options are needed to reduce the impact of motor vehicles on climate change and declining fossil fuel resources. Cars which are fueled by hydrogen could be a sustainable method of transportation if suitable technologies can be devised to produce hydrogen in an environmentally benign manner along with the provision of the necessary fueling infrastructure. This paper assesses size, space, and cost requirements of bioreactors as a decentralized option to supply hydrogen powered cars with biohydrogen produced from algae or cyanobacteria on a theoretical basis. Decentralized supply of biohydrogen could help to reduce the problems that hydrogen cars face regarding market penetration. A feasibility study for decentralized biohydrogen production is conducted, taking the quantity of hydrogen which is needed to fuel current hydrogen cars into account. While this technology is, in theory, feasible, sizes, and costs of such reactors are currently too high for widespread adoption. Thus, more R&D is needed to close the gap and to approach marketability.